Short incubation periods in Campylobacter outbreaks associated with poultry liver dishes - Hope, Kirsty G; Merritt, Tony D; Durrheim, David N (Communicable Diseases Intelligence, 2014)
This article describes a point source outbreak of Campylobacter associated with duck liver parfait with a possible short incubation period; and the review of the literature prompted by the investigation, which identifies short incubation periods as a common feature of point source outbreaks associated with poultry liver consumption.